Qualitative inquiry of educational experiences: ‘Transmedia:#elcontenidodelfuturo’ and ‘The Grammar Army’: Qualitative inquiry of educational experiences: ‘Transmedia:#elcontenidodelfuturo’ and ‘The Grammar Army’ - PEÑA-ACUÑA, Beatriz; JIMÉNEZ-HERNÁNDEZ, David (Utopía y Praxis Latinoamericana, 2021)
The objective of this inquiry targets to discover the appreciation of educational experiences of teachers who participate in two projects of the Comunica Program developing strategies and skills. These designs are characterized by innovating through transmedia formats that are attractive to these generations. The method is qualitative by analyzing the results of the responses contained in an online form of open questions to a sample of 34 teachers at the levels of Primary Education and Baccalaureate of Andalusia in Spain during 2019-2020. The results show six dimensions with positive results regarding the perception of these variables worked on in these two case projects. Among the emerging subdimensions, it is highlighted attractive teaching strategies, interaction, transversality, as well as indicators such as motivation and fun of students and teachers stand out.